1989
DOI: 10.3382/ps.0680496
|View full text |Cite
|
Sign up to set email alerts
|

Diclazuril, a New Broad Spectrum Anticoccidial Drug in Chickens.

Abstract: Battery trials have confirmed the broad spectrum anticoccidial activity of diclazuril as previously reported in dose titration studies. The advocated dose level of 1 ppm in the diet demonstrated excellent activity against the economically most important Eimeria species. At this dose level, body weight gains were comparable to those of uninfected, unmedicated controls and the oocyst production was negative in most species. Lesion scores and dropping scores were nil or highly reduced. An E. maxima-147 strain, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…To demonstrate the effect of diclazuril in battery and floor pen trials with chickens for fattening, the applicant submitted three studies published by Vanparijs et al (1989aVanparijs et al ( , b, 1990 performed with diclazuril from Clinacox ® .…”
Section: Battery and Floor Pen Trials With Artificial Single And Mixementioning
confidence: 99%
See 3 more Smart Citations
“…To demonstrate the effect of diclazuril in battery and floor pen trials with chickens for fattening, the applicant submitted three studies published by Vanparijs et al (1989aVanparijs et al ( , b, 1990 performed with diclazuril from Clinacox ® .…”
Section: Battery and Floor Pen Trials With Artificial Single And Mixementioning
confidence: 99%
“…A dose titration study in chickens (Vanparijs et al, 1989a) indicated that diclazuril at dosages of 0.5 to 10 mg/kg feed was highly active against all major pathogenic species (E. tenella, E. acervulina, E. necatrix, E. brunetti, E. maxima and E. mitis) and effective in terms of weight gain, suppression of mortality, dropping scores and oocyst counts. An effective dose range of 1 to 10 mg/kg feed was identified after mixed infections with E. tenella and E. acervulina or E. necatrix and E. brunetti in a floor pen study.…”
Section: Battery and Floor Pen Trials With Artificial Single And Mixementioning
confidence: 99%
See 2 more Smart Citations
“…To demonstrate the effect of diclazuril in battery and floor pen trials with turkeys for fattening, the applicant submitted three studies published by Vanparijs et al (1989aVanparijs et al ( , b, 1990 performed with diclazuril from Clinacox ® .…”
Section: Battery and Floor Pen Trials With Artificial Single And Mixementioning
confidence: 99%